A rare cause of interstitial lung disease with skin lesion - Smera Ramakrishnan; Spandana P Hegde; Manjunath Shenoy Mala; Nazir Attar (Wolters Kluwer Medknow Publications, 2022)
We report a case of an interstitial lung disease of unknown etiology in a middle-aged man who later presented with skin lesions on the upper back. Histopathological examination showed noncaseating granulomas suggesting a possibility of cutaneous sarcoidosis. With further workup that included histopathology, the diagnosis of sarcoidosis was established. Sarcoidosis is a multisystem granulomatous disease of unknown etiology primarily affecting the lungs and intrathoracic lymph nodes but can affect virtually any organ. In our case, appearance of cutaneous lesion and further workup lead to the diagnosis of sarcoidosis.